PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada PT Bank OCBC NISP Tbk. KCP Bekasi) - Putra, Sakra Brahma; Yuniawan, Ahyar (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyzing variable influence situational leadership style, work environment andwork motivation againstemployee performance. This study was conducted at PT Bank OCBC NISP Tbk. KCP Bekasi. The number of samples was estabilished by 60 respondents with the sample using methods simple random sampling. Measurement in kuisioner using likert scale. Methods of analysis data is used path analysis with assistance SPSS program version 21 for test influence mediation used Sobel test. The testing of hypotheses, indicate that situational leadership style variable are positive and significant effect againstemployee performance with regressioncoefficients of 0,314. With the most dominant on employee performance dimension of situational leadership style is delegating 49.6%. Work environment are positive and significant effect against employee performance with regressioncoefficients of 0,222. Positive effect on situational leadership style against employee performance through work motivation by results test indicate t value of 2,60. Positive effect on work environment against employee performance through work motivation by results test indicate t value of 4,57. Results test with Sobel test showed the t value is greater than t table at 5% level is 2.00. The results of path analysis showing that directlyinfluence situational leadership styleagainst employee performance of0,314 and indirect influence through the work motivationof 0,667.Directly influence work environment against employee performance of 0,222 and indirect influence through the work motivation of 0,908.